Influence of the auditory system on pressure distribution in the ear canal - García-González, Antonio Luis; Castro Egler, Cristina; González-Herrera, Antonio (World Scientific Publishing Company, 2018)
The pressure gain distribution along the ear canal is strongly dependent on boundary conditions, and, in normal conditions, the ear canal produces a 0–20-dB pressure gain close to the tympanic membrane in the 0.1–20kHz range. Additionally, the pressure gain distribution along the ear canal at high frequencies (over the second resonance of the ear canal at 8–9kHz) depends strongly on axis position; therefore, the middle ear transfer functions based on ear canal pressure are also strongly dependent on the measuring point. Objective: The aim of this study is to evaluate the mechanical influence of the tympanic cavity, ossicular chain and tympanic membrane connections on the pressure in the ear canal in the frequency range of 0.1–20kHz when a pressure source is applied to the ear canal entrance. Methods: We have developed numerical simulations for seven different models using the finite element method (FEM). Starting with an external ear canal finite element model, additional elements are coupled or removed to evaluate their contributions. We modeled and simulated the tympanic membrane, ossicular chain, tympanic cavity and a simplified cochlea in seven different combinations. Results: The pressure distribution along the external ear canal is obtained and represented in the 0.1–20kHz range for the seven model configurations
Keywords: Presión - Medición; Ear canal; resonance; Middle ear; Tympanic membrane; Tympanic cavity; Finite element analysis; Resonance